Global public goods: a concept for framing the post-2015 agenda? - Inge Kaul (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Looking at today's policy challenges in richer and poorer countries through the analytical lens of global public goods (GPGs), including the links between GPG provisioning and development, this paper suggests a three-pronged approach for the framing of the Post-2015 Agenda: (1) to organise the Agenda process as a recurrent global policy loop that starts at the national level, with the preparation of national programmes of international cooperation by industrialised and developing countries; (2) to promote global fairness, notably process fairness, in order to allow all concerned to have an effective voice in matters that concern them; and (3) to take full advantage of the new resource-mobilisation opportunities that some GPGs present. If approached in this way, the Post-2015 Agenda would primarily be an agenda of international cooperation commitments. It would do more than call for goals such as `halving poverty' or `mitigating climate change' – and then remain silent on who would do what in order to progress towards these goals. Rather, the Agenda would equip countries to actually progress towards more inclusive and sustainable growth and development – nationally, regionally and globally.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen; Regionale + globale + transnationale Governance